2022
DOI: 10.1002/celc.202101279
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the PTFE Membrane Thickness on the CO2 Electroreduction Performance of Sputtered Cu‐PTFE Gas Diffusion Electrodes

Abstract: Gas diffusion electrodes (GDE) obtained by sputtering metal films on polytetrafluoroethylene (PTFE) membranes are among the most performant electrodes used to electrochemically reduce CO2. The present work reveals several essential aspects for fabricating performant PTFE‐based gas diffusion electrodes (GDEs) for CO2 electroreduction (CO2R). We show that adding an additive layer (a mixture of carbon and Nafion™ or Nafion™ only) is required for stabilizing the metal catalyst film (Cu), deposited via sputtering o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 22 publications
0
20
0
1
Order By: Relevance
“…As a stark contrast, the carbon‐fibre‐based electrode only lasts for less than one hour under identical reaction conditions [11a] . However, the PTFE substrate itself is not conductive, and the catalyst loaded on top has been found to detach easily (even at low current densities) [34] . For these reasons, the PTFE‐based electrode usually needs to be coated with an additive layer (e.g., graphite, carbon or metal) to enable the transport of electrons and stabilise the catalyst in the application [11a, 34] .…”
Section: Electrode Construction For Gas Reduction Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a stark contrast, the carbon‐fibre‐based electrode only lasts for less than one hour under identical reaction conditions [11a] . However, the PTFE substrate itself is not conductive, and the catalyst loaded on top has been found to detach easily (even at low current densities) [34] . For these reasons, the PTFE‐based electrode usually needs to be coated with an additive layer (e.g., graphite, carbon or metal) to enable the transport of electrons and stabilise the catalyst in the application [11a, 34] .…”
Section: Electrode Construction For Gas Reduction Reactionsmentioning
confidence: 99%
“…However, the PTFE substrate itself is not conductive, and the catalyst loaded on top has been found to detach easily (even at low current densities) [34] . For these reasons, the PTFE‐based electrode usually needs to be coated with an additive layer (e.g., graphite, carbon or metal) to enable the transport of electrons and stabilise the catalyst in the application [11a, 34] . This foreign layer, however, might increase the interfacial resistance and impact the reaction environment, potentially lowering the gas reduction performance.…”
Section: Electrode Construction For Gas Reduction Reactionsmentioning
confidence: 99%
“…Dadurch ergeben sich über die Entwicklung von Katalysatoren und GDEs hinaus neue Forschungs-und Kooperationsmöglichkeiten. [20][21][22] Bei der Entscheidung, welche Reaktionen zu beobachten sind, ist es wichtig, dass Wissenschaftler:innen sich der Wechselwirkungen zwischen Anode und Kathode bewusst sind. Die Chemie an Anode, Membran und Elektrolyt beeinflusst die Kathode und umgekehrt.…”
Section: Elektrolysezellenunclassified
“…27 Non-conductive GDLs based on polytetrafluoroethylene (PTFE) have become popular only recently and provide higher flooding resistance and achieve more stable conditions with improved CO 2 RR activity. 23,[28][29][30][31][32] On top of the GDLs, a coating of the active catalytic layer needs to be airbrushed, 33 doctor-bladed, 34,35 sputtered 32,36,37 or electrochemically deposited [38][39][40] to achieve a porous 3D composite structure. Luo et al 41 reported a manufacturing strategy to enhance the CO 2 RR activity by electrochemical deposition of a porous Zn catalyst on a Cu substrate and turning the metal structure into a GDE by fine-tuning with hydrophobic parts.…”
Section: Introductionmentioning
confidence: 99%